The Hypothesis of the Arsacids’ Descent from the Achaemenids: Myth or Reality? - Arthur Melikyan (Banber Arevelagitut'yan Instituti, 2025)
In the 40s of the last century, J. Wolski proposed a thesis, still dominant in historiography, arguing that the story of Arrian which reached us thanks to his work “Parthica” that the Arsacid dynasty, the founder of Parthian state, descended from the Achaemenids, has a fictional origin. According to J. Wolski, J. Neusner and their followers, it is an "ideological fiction", a "literary forgery", which appeared in the period between the second half of II century BC and the beginning of the I century AD and was recorded in written form by Arrian. However, the conclusion, based on the limited and often one-sided data by Strabo and Justin, is defective and does not meet the current requirements of the study of the problem. Оnly a comprehensive examination of the evidence provided by written sources in the field of the Parthian numismatics, epigraphy, archaeology, onomastics and other branches of science can give a complete answer to the issue. In this case, it becomes obvious that the "Arrianian" legend about the genealogical connection between the Arsacids and the Achaemenids is not just a literary fiction, but has a real historical basis.